Berczeli Anzelm Károlyhoz - Horpácsi Sándor (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1973)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek